2022
DOI: 10.1126/science.abn6012
|View full text |Cite
|
Sign up to set email alerts
|

Hydrotrioxide (ROOOH) formation in the atmosphere

Abstract: Organic hydrotrioxides (ROOOH) are known to be strong oxidants used in organic synthesis. Previously, it has been speculated that they are formed in the atmosphere through the gas-phase reaction of organic peroxy radicals (RO 2 ) with hydroxyl radicals (OH). Here, we report direct observation of ROOOH formation from several atmospherically relevant RO 2 radicals. Kinetic analysis confirmed rapid RO 2 + OH reactions forming ROOOH, with rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 65 publications
(40 reference statements)
1
27
0
Order By: Relevance
“…183 For the isoprene−OH oxidation system, the molar yield of ROOOH was estimated to be around 1%, with an averaged lifetime of minutes to hours. 183 Given their high oxygenation level, relatively high reactivity in the atmosphere, and the capacity of producing singlet molecular oxygen ( 1 O 2 ), 183 impacts from ROOOH on atmospheric oxidation capacity, new particle formation, global climate, and adverse health outcomes are waiting to be investigated in the future.…”
Section: Other Formation Pathways For Posmentioning
confidence: 99%
“…183 For the isoprene−OH oxidation system, the molar yield of ROOOH was estimated to be around 1%, with an averaged lifetime of minutes to hours. 183 Given their high oxygenation level, relatively high reactivity in the atmosphere, and the capacity of producing singlet molecular oxygen ( 1 O 2 ), 183 impacts from ROOOH on atmospheric oxidation capacity, new particle formation, global climate, and adverse health outcomes are waiting to be investigated in the future.…”
Section: Other Formation Pathways For Posmentioning
confidence: 99%
“…Besides the environmental conditions, the prior studies reported that the product of the reaction of RO 2 with OH, trioxides (ROOOH), might lead to an OH interference signal. The reactions of RO 2 radicals with OH radicals might be competitive with other sinks for RO 2 radicals (Fittschen, 2019;Fittschen et al, 2019;Berndt et al, 2022). Fittschen et al (2019) reported that the OH interference signals might come from the ROOOH heterogeneous decomposition on the walls of the FAGE cell or the entrance nozzle, but they also noted that the ROOOH interference is highly dependent on the design and measurement conditions of different FAGE instruments.…”
Section: The Oh and Ho 2 Measurementsmentioning
confidence: 99%
“…Therefore, oxidation of nicotine forms P1, P2, P4, P5, and P6 with fractional yields of 0.55, 0.25, 0.12, 0.03, and 0.05 if initiated by OH radical (with fractions of R1, R3, and R6 based on ROCBS-QB3 barrier heights) or forms P1, P2, and P4 with fractional yields of 0.62, 0.32, and 0.06 if initiated by ozone (with fractions of R1 and R6 based on RCCSD­(T)/aVDZ barrier heights). Rapid hydrogen atom transfers (HATs) activated by the amine-N-center are also found in recent studies on atmospheric oxidation of amines. …”
Section: Resultsmentioning
confidence: 86%